Spinal cord injury transiently alters Meissner’s corpuscle density in the digit pads of macaque monkeys - Crowley, Matthew (J Comp Neurol, 2019)
Meissner’s corpuscles (MCs) are cutaneous mechanoreceptors found in glabrous skin and are exquisitely sensitive to light touch. Along with other receptors, they provide continuous sensory feedback that informs the execution of fine manual behaviors. Following cervical spinal deafferentation injuries, hand use can be initially severely impaired, but substantial recovery occurs over many weeks, even when ~95% of the original input is permanently lost. While most SCI research focuses on central neural pathway responses, little is known about the role of peripheral receptors in facilitating recovery. We begin to address this by asking the following: (1) What is the normal pattern of MCs in the distal pads of all five digits in the macaque monkey (with hands similar to humans)? (2) What happens to these receptors 4–5 months following either a dorsal column lesion (DCL) or a combined dorsal root/dorsal column lesion (DRL/DCL), when functional recovery is largely complete? (3) What happens chronically, 12–14 months later? Our findings show that in normal monkeys, MCs are densest in the distal pads of the opposing thumb and index finger, with the greatest concentration on the thumb. This reflects a close functional relationship between receptor density and precision grip. At 4–5 months post-injury, there was a (~30%) loss of MCs on the deafferented digits of the injured hand compared with the contralateral side. However, 12–14 months after a DRL/DCL, receptor densities had returned to normal levels. Our findings indicate a complex peripheral response and highlight the importance of the periphery in shaping central changes.